ANALISA KAPASITAS KOLOM PIPIH TERHADAP BEBAN GRAVITASI DENGAN DIAGRAM INTERAKSI - Violeta, Iona (Fakultas Teknik Universitas Panca Bhakti, 2023)
Utilization of column structures is generally a square shape with quite large dimensions. Therefore, it is necessary to use flat columns to adjust the width of the walls. The reduction of room space caused by the enormous dimensions of column could be solved. In addition, both exterior and interior aesthetics can be applied without affected by the large-dimensional columns. On the other hand, flat column has stiffness difference in its two main axes results to the strength capacity and stability of the entire structure. Thus, this research is delivered to study the flat column strength capacity with 3 variances, specifically with 10cmx90cm of dimensions, 15cmx60cm of dimensions, and 20cmx45cm of dimensions, and also 1 variance of conventional square column with 30cmx30cm of dimensions, in which all has total area of 900cm2. The analysis results in 10cmx90cm of flat column is not safe since some force combinations were being outside the cover of interaction curve on its weak axis. While on the 15cmx60cm of dimensions and 20cmx45cm of dimension flat columns, there were some force combinations reach the threshold of the curve cover on the weak axes, but generally can still be considered as safe. Therefore, flat column may be used in the structure design but the flatness ratio should be carefully considered since the huge inequality of its strength capacity on the strong axis and weak axis.